Penyuluhan Hukum Pertanahan Desa Bottopenno Kabupaten Wajo - Ismail Ali; Chandra Anugerah; Aditya Sani; Febri Wulansari; Andi Bau Muddariah; Andi AdeLiah Ramadani (YP-SDI Lamaddukelleng, 2025)
Land Law Counseling in Bottopenno Village, Majauleng District, Wajo Regency is a community service research within the Real Work Lecture (KKN) as a form of implementation of the Tri Dharma of Higher Education. This counseling was conducted to increase community understanding regarding land in order to reduce or prevent the emergence of land disputes. In addition, this counseling aims to provide solutions to resolve disputes that are currently occurring in the community. The counseling method is carried out by initial observation of the problems that occur, followed by the provision of materials and discussions. The results of this counseling have succeeded in increasing the understanding and insight of the Bontopenno Village community regarding land law issues